2018
DOI: 10.1186/s13054-017-1922-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of long-term outcome in ICU survivors: results from the FROG-ICU study

Abstract: BackgroundIntensive care unit (ICU) survivors have reduced long-term survival compared to the general population. Identifying parameters at ICU discharge that are associated with poor long-term outcomes may prove useful in targeting an at-risk population. The main objective of the study was to identify clinical and biological determinants of death in the year following ICU discharge.MethodsFROG-ICU was a prospective, observational, multicenter cohort study of ICU survivors followed 1 year after discharge, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 33 publications
10
145
0
3
Order By: Relevance
“…However, we did observe that TT was associated with a significant increase of ICU length of stay. ICU length of stay is a known independent factor ; the mean score of the general population is 50; one standard deviation is marked in grey associated with increased stationary healthcare use and 1-year mortality after ICU discharge and should be considered when deciding for the best time point of TT in critical ill patients [24,25]. In our study, associations observed in univariate analyses were lost mainly due to the strong confounding effect of ICU length of stay.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, we did observe that TT was associated with a significant increase of ICU length of stay. ICU length of stay is a known independent factor ; the mean score of the general population is 50; one standard deviation is marked in grey associated with increased stationary healthcare use and 1-year mortality after ICU discharge and should be considered when deciding for the best time point of TT in critical ill patients [24,25]. In our study, associations observed in univariate analyses were lost mainly due to the strong confounding effect of ICU length of stay.…”
Section: Discussionmentioning
confidence: 72%
“…For all 1205 patients, the median duration of mechanical ventilation was 16 days (IQR 10-27) and that of ICU length of stay 22 days (IQR 14-36). The median duration of ventilation (20 days [IQR [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] vs. 11 days [IQR 6-16], p < 0.001) and ICU stay (p < 0.001, Table 1) was twice as long for tracheotomised patients. Primary 877 ARDS patients survived and discharged from ICU.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term outcome of critically ill patients after discharge from the ICU depends on manifold clinical and biological factors, including age, comorbidity, and length of stay at the ICU. 28 The association between copeptin plasma levels and overall mortality suggests that copeptin could be a sensitive biomarker for the accurate assessment of the initial disease severity, supporting that the copeptin-related pathologies as biological stress and hypoperfusion are major determinants of the severity of critical illness. Future studies should prospectively evaluate, whether the implementation of copeptin measurements into multifactorial risk models could improve prognostication and thereby management of critically ill patients.…”
Section: Discussionmentioning
confidence: 97%
“…More strikingly, copeptin plasma concentrations at the admission to the ICU even predicted the long‐term, overall mortality of critically ill patients in our study. The long‐term outcome of critically ill patients after discharge from the ICU depends on manifold clinical and biological factors, including age, comorbidity, and length of stay at the ICU . The association between copeptin plasma levels and overall mortality suggests that copeptin could be a sensitive biomarker for the accurate assessment of the initial disease severity, supporting that the copeptin‐related pathologies as biological stress and hypoperfusion are major determinants of the severity of critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Overall hospital mortality of critically ill patients has been reported to range from 13.5% to 31%, and it has been the subject of extensive research in order to understand which patients are at a higher risk of dying . The survival curve related to Intensive Care Unit (ICU) admission is known to be determined in the short term by characteristics of the acute illness and the related residual organ dysfunction and by individual characteristics, like age and comorbidities in the long term . Multiple other determinants of post‐ICU early mortality have been described which are related to the resource capacity of the hospital and how those resources are organized.…”
Section: Introductionmentioning
confidence: 99%